2011
DOI: 10.1177/0333102411424619
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of trigeminal neuralgia and persistent idiopathic facial pain: A population-based study

Abstract: This large population-based study revealed that TN and PIFP are rare facial pain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(131 citation statements)
references
References 13 publications
7
119
1
4
Order By: Relevance
“…However, in trigeminal neuralgia the finding of lateralization persists and is reconfirmed by the study of Bangash. A recent population based study showed similar result with 60% of confirmed trigeminal neuralgia cases were affected on the right side (7). In this study female predominance (70%) was also reported, which is in line with the study by Bangash (7).…”
Section: Dear Editorsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in trigeminal neuralgia the finding of lateralization persists and is reconfirmed by the study of Bangash. A recent population based study showed similar result with 60% of confirmed trigeminal neuralgia cases were affected on the right side (7). In this study female predominance (70%) was also reported, which is in line with the study by Bangash (7).…”
Section: Dear Editorsupporting
confidence: 91%
“…A recent population based study showed similar result with 60% of confirmed trigeminal neuralgia cases were affected on the right side (7). In this study female predominance (70%) was also reported, which is in line with the study by Bangash (7). Unfortunately, the genuine pathophysiologcial origin of this phenomenon remains unknown.…”
Section: Dear Editorsupporting
confidence: 90%
“…1 Trigeminal neuralgia is defined as a recurrent unilateral brief electric shocklike pain, abrupt in onset and termination, limited to the distribution of one or more divisions of the trigeminal nerve and triggered by innocuous stimuli. 2 The pain is usually triggered by sensory stimuli to the skin, mucosa, or teeth that are innervated by the ipsilateral trigeminal nerve.…”
mentioning
confidence: 99%
“…Die Personen mit einer chronischen Migräne unterschieden sich in Alter, BodyMass-Index, Ausbildung und Rauchverhalten von den Patienten mit einer episodischen Migräne [21]. In einer Subgruppe dieser Studie wurden auch die Lebenszeitprävalenzen der Trigeminusneuralgie (0,3 %) und des persistierenden idiopathischen Gesichtsschmerzes (0,03 %) erhoben [29].…”
Section: Epidemiologieunclassified